The Role Of Imports In Development According To Islamic And Conventional Macroeconomic Perspectives - Hartin Nst, Venny Fraya; Abd. Majid, M. Shabri; Harahap, Isnaini (Universitas Ibn Khladun Bogor, 2024)
Indonesia as a developing country is expected to always make developments by carrying out development in all fields to achieve a prosperous country. However, because the source of financing for national development is not small, apart from foreign exchange reserves, the source of financing and funding for a country's national development is foreign debt that the country borrows from other countries. Aspects of international trade, especially in the field of export-import, which will be the topic of discussion in this scientific research, this research methodology as a whole is a type of descriptive-analytical research with qualitative research. Research results as follows 1) The role of imports in Islamic macroeconomic development is very important because Indonesia's imports which include oil and gas imports and non-oil and gas imports all come from the world's earth, especially oil and gas imports must be limited to domestic needs that are needed by the community, especially fuel; 2) The role of imports in conventional macroeconomic development is also quite important in the life needs of Indonesian society; 3) The government as the policy maker of Indonesian Imports, must see and supervise Indonesian imports by issuing new policies on Indonesian Imports so that government and private companies do not monopolize in importing goods into Indonesia.